“As Marias indígenas” : a Lei Maria da Penha no universo indígena de Roraima - Rodrigues, Karolayne Mota (2019)
After an intense struggle on the part of the women's movement and supporters of the cause, Brazil enacted in 2006 Law 11.340 / 06, popularly known as Lei da Penha. Since then, much research has been done to analyze its applicability in the national scenario. However, it is necessary to undertake research, both quantitative and qualitative, in order to understand the applicability of this law in an indigenous context. This, therefore, is the main objective of this text, to analyze the applicability of the Maria da Penha Law in the indigenous context, through a process and a judicial decision, as well as discussion wheels on the subject, an anthropological report, as well as other experiences, in order to understand how the State has dealt with this issue. It also seeks to analyze in which the Maria da Penha Law conforms to the cultural specificities of indigenous communities and proposes an action that will enhance the effectiveness of the Maria da Penha Law with indigenous women. After an analysis of the material in hand, it is possible to attest to the need to clarify to the indigenous communities the details of the Maria da Penha Law, with a view to a conscious and informed decision. Moreover, it is noticeable, remnants of an indigenist policy of assimilation and integrationist, in force until the end of the twentieth century. In addition, it showed how indispensable is the form of anthropological reports in criminal prosecutions involving indigenous people, in the sense of understanding how they deal and perceive a certain "wrongful". It has also been shown how the issue of domestic violence in communities overflows the borders of the family, they are collective, it involves all those who live and share the same community.